Electrically Tunable Selective Reflection of Light from Ultraviolet to Visible and Infrared by Heliconical Cholesterics. (27th March 2015) - Xiang, Jie; Li, Yannian; Li, Quan; Paterson, Daniel A.; Storey, John M. D.; Imrie, Corrie T.; Lavrentovich, Oleg D.
<x xml:space="preserve">Abstract</x> Electrical tuning of selective reflection of light is achieved in a very broad spectral range from ultraviolet to visible and infrared by an oblique helicoidal state of a cholesteric liquid crystal in a wide temperature range (including room temperature). The phenomenon offers potential applications in tunable smart windows, lasers, optical filters and limiters, as well as in displays.